Escrita, arte-poesia e política: a composição coletiva enquanto processo de criação e potência feminista - Jó, Ingrid Cerantola (Universidade Federal de São Carlos, 2023)
This work reflects on a joint construction process of writing~research~art~knowledge and its contrast with academic training. Based on the description of the process of creating a book created by many hands by researchers from imuê - Instituto Mulheres e Economia - and by Andréa Guerreira, multi-artist and coordinator of the cultural group Boi Mandingueiro, located in Mata do Ronca, on the border between Olinda, Paulista and Recife, in Pernambuco-BR, I seek to echo, together with the feminist literature on the construction of knowledge, expression and writing, about experiments that take into account the political~artistic~poetic~affective crossings that permeate the creation between cultures, bodies and miscellaneous languages. Then, from the review of the Pedagogical Project of the UFSCar Social Sciences course, I make a counterpoint between my graduation experience and other research/writing proposals that inspire and expire contrasting narrative to Eurocentric biases, individualized and embedded in a colonizing logic , racist, patriarchal and cisheteronormative. This work raises the question of how to produce counter-narratives from the paths of women~resistance in society, popular culture, artists, poets, researchers, through the collective composition that is exercised in the daily struggle, poetic uprisings and transcription in Pernambuco.
Writing, art-poetry and politics: collective composition as a process of creation and feminist power
Keywords: Feminismo; Feminism; Mulheres; Women; Contra-narrativas; Counter-narratives; Escrita; Writing; Arte; Art; Cultura popular; Culture; CIENCIAS HUMANAS::ANTROPOLOGIA